Determinant of stunting among children under-five years: A nationwide study in Zambia - Muhammad Abi Zakaria; Kusnanto Kusnanto; Ika Nur Pratiwi; Hidayat Arifin; Doreen Phiri; Agostinha Soares; Kittisak Kumpeera (The Journal of Palembang Nursing Studies, 2024)
Background: Stunting cases among children represent one of the most serious issues in human development. Zambia, in particular, has a higher number of stunting cases in Africa.Objective: The purpose of this research was to analyze the prevalence and determinant of stunting among children under-five years in Zambia. Methods: This study utilized data from the 2018 Zambia Demographic Health Survey (ZDHS), with a total of 1,710 surveys selected. We observed variables related to mothers, children, and the environment to assess stunting. Chi-Square and Binary Logistic Regression were used for data analysis.Results: A total of 22,16% children under five years in Zambia had a stunting. We found that factors such as low birth weight (<2500 grams) (OR = 3.24; 95% CI = 2.163-4.869), mothers with no education (OR = 1.80; 95% CI = 0.681-4.760), those with the poorest wealth index (OR = 2.30; 95% CI = 1.341-3.943), intervals between previous children less than 24 months (OR = 1.58; 95% CI = 1.107-2.270), and breastfeeding for more than 6 months (OR = 4.499; 95% CI = 3.179-6.67) were associated with a higher likelihood of stunting in Zambia.Conclusions: Our study demonstrates that stunting is associated with family and household factors, as well as breastfeeding practices. Policymakers should consider implementing structured policies to address stunting, particularly for expectant mothers, as a long-term solution.